2019
DOI: 10.1161/jaha.118.009122
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Temporal Changes of Heart Failure Among 5‐Year Childhood Cancer Survivors: a DCOG‐LATER Study

Abstract: Background Heart failure is one of the most important late effects after treatment for cancer in childhood. The goals of this study were to evaluate the risk of heart failure, temporal changes by treatment periods, and the risk factors for heart failure in childhood cancer survivors ( CCS ). Methods and Results The DCOG‐LATER (Dutch Childhood Oncology Group–Long‐Term Effects After Childhood Cancer) cohort includes 6,165 5‐year CCS diagnosed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 34 publications
0
83
0
1
Order By: Relevance
“…Notably, the risk for heart failure was observed to further decrease from the 1980s into the 1990s, suggesting a favorable trend. In contrast, Dutch investigators recently reported that survivors from the 1970s had a lower cumulative incidence of heart failure compared with those treated in the 1980s and 1990s 22. However, the temporal pattern of reduction in exposure to radiotherapy (defined as maximum prescribed heart dose) in Dutch survivors was of a smaller magnitude (with no chest radiotherapy ranging from 65.6% in the 1970s to 82.2% in the 1990s) than in the Childhood Cancer Survivor Study cohort (ranging from 23% to 60%) utilizing detailed heart dosimetry measurements.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, the risk for heart failure was observed to further decrease from the 1980s into the 1990s, suggesting a favorable trend. In contrast, Dutch investigators recently reported that survivors from the 1970s had a lower cumulative incidence of heart failure compared with those treated in the 1980s and 1990s 22. However, the temporal pattern of reduction in exposure to radiotherapy (defined as maximum prescribed heart dose) in Dutch survivors was of a smaller magnitude (with no chest radiotherapy ranging from 65.6% in the 1970s to 82.2% in the 1990s) than in the Childhood Cancer Survivor Study cohort (ranging from 23% to 60%) utilizing detailed heart dosimetry measurements.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the above global evaluations, we also illustrated some of our predictions for well-established and frequently used antineoplastic drugs with known cardiovascular side effects. As the most common chemotherapy approach, anthracycline-involved treatment improves overall survival but may induce severe or life-threatening heart failure in some individuals ( 5 , 60 ). Mechanistically, anthracycline can cause dose-dependent cardiotoxicity by redox cycling and free-radical formation mediated by topoisomerase-IIβ ( 6 , 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The common clinical complications are asymptomatic pericarditis, congestive heart failure, and heart infarction. Even though clinicians have to give particular attention to these complications, anthracycline treatment [60][61][62]) is an additional major risk factor for additional cardiotoxicity during radiotherapy with a synergistic effect. However, the use of anthracycline, other cardiotoxic chemotherapies, immunotherapy [63][64][65] and targeted therapies [66,67] should only be used with great caution and only after carrying out a careful treatment plan and optimization [1,30,40].…”
Section: Discussionmentioning
confidence: 99%